Tunay na repormang agraryo ipaglaban! (Quezon City Asia Visions, 1988)
A documentation of the three-day Agrarian Reform Express from Northern and Southern Luzon to Manila staged by various peasant groups in protest of the then proposed Agrarian Reform Bill in Congress.
VHS
Keywords: Land reform -- Philippines